Depressive Symptoms Among University Undergraduates In Southeast Nigeria: The Predictive Effects Of Pathological Gambling And Social Media Addiction - Elechi, Kennedy Ndubuisi; Okoye, Chukwuemeka A.F (Practicum Psychologia, 2024)
The study explored pathological gambling and social media addiction as predictors of depressive symptoms among university undergraduates in southeast Nigeria. Four hundred and sixty (460) participants, comprising 280 (60.9%) males and 180 (39.1%) females who were selected through purposive sampling technique participated in the study. Their ages ranged from 18 to 24 years, with a mean age of 20.5 years and standard deviation of 4.5 years. The instruments used for data collection were South Oaks Gambling Screen, Internet Addiction Test and Beck Depression Inventory. The design adopted in the study was a predictive design while multiple linear regression was adopted for data analysis. Three hypotheses were tested, and the result revealed that the first hypothesis which stated that pathological gambling would significantly predict depressive symptoms among university undergraduates was accepted at F = 216.706, β=.572: t =15.062, P<.01. Also, the second hypothesis which stated that social media addiction would significantly predict depressive symptoms among university undergraduates was accepted at F= 216.706, β=.221; t =5.818, P<.01. Furthermore, the third hypothesis which stated that Pathological gambling and social media addiction would jointly and significantly predict depressive symptoms among undergraduates was accepted at F = 216.706, R = .702, R2 = .492, p< .01. Based on the findings, the researchers recommended among others that that Students should be given proper orientation about the psychological and economic negative implications of gambling.